Customary Land Pawn Disputes in Lebung Jangkar Village: An Islamic Law and Cultural Perspective - Moh. Hidayatullah A.K. Husein; Anggar Putra; Putri Rahyu; Abdul Fajri Kolopita (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2025)
Prolonged agricultural land pawn practices in indigenous communities often create structural inequalities and recurring disputes due to unclear legal boundaries. This article examines the dynamics of customary land rights (hak ulayat) in agricultural land pawn practices and the resolution of related disputes within the indigenous community of Lebung Jangkar Village. Land is perceived as ancestral heritage with strong social and cultural significance, making pawn practices socially accepted as temporary economic instruments without transferring ownership. However, extended pawn periods and the continuous utilization of pawned land by pawn recipients frequently result in unequal power relations and latent agrarian disputes. Focusing on rice field pawn disputes, this study analyzes the relationship between customary land rights, pawn practices, and dispute resolution through traditional elders (kriye). Using a qualitative normative-empirical approach through interviews, observation, and document analysis, the study finds that dispute resolution through the kriye functions as an effective living law grounded in deliberation, social harmony, and substantive justice, substantively aligning with the Islamic legal principles of ṣulḥ and rahn. Nevertheless, the absence of written documentation and the weak integration of Article 7 of Law Number 56 of 1960 indicate the need for greater normative harmonization to ensure legal certainty and equitable protection for customary landholders.